Asthma features in severe COPD: Identifying treatable traits. (December 2018) - Matthes, Sandhya; Stadler, Jakob; Barton, Jürgen; Leuschner, Gabriela; Munker, Dieter; Arnold, Paola; Villena-Hermoza, Heidrun; Frankenberger, Marion; Probst, Philipp; Koch, Andrea; Kneidinger, Nikolaus; Milger, Katrin; et al.
Abstract: Aim: Biological therapies developed for severe asthma may have a role in COPD patients with asthma features. Method: We carried out a prospective, consecutive, cross-sectional analysis of 80 patients with severe COPD GOLD IV/D. Results: We studied 80 patients (48.8% female), aged 57.6 ± 5.1 years, ex-smokers with 35.7 ± 21.2 pack years, BMI 22.3 ± 3.5 kg/m 2, FEV1 of 0.61 ± 0.2 L (21.1 ± 5.6% pred), pO2 52.4 ± 8.4 mmHg, and BODE 6.9 ± 1.7. 68% had >2 moderate or severe exacerbations annually. 16.1% (5/31) patients showed FEV1 reversibility of >12% and >200 ml despite maximal therapy, 33% (15/45) had FENO ≥22.5 ppb, 33% (24/73) had serum IgE ≥100 I.E./ml and there was positive allergen sensitization in 51.5% (35/68). Blood eosinophilia of ≥150 cells/μl was seen in 47% (35/74). Induced sputum showed eosinophilia of ≥2% in 56% (14/24) with respiratory pathogens in 63.8% (30/47). We identified 12 (15%) patients with asthma-COPD overlap. Of these, 10 (83.3%) had frequent exacerbations and these patients had significantly more severe exacerbations requiring NIV or ICU than those without asthma features (p < 0.005). Conclusion: We detected asthma features in a substantial subset of stable patients with severe COPD. Asthma features were associated with more severe exacerbation despite optimal COPD therapy, representing potential candidates for targeted therapy with anti- IgE or anti-IL5. Highlights: Asthma features are common in severe chronic obstructive pulmonary disease (COPD). COPD patients with asthma overlap have more severe exacerbations. Asthma COPD overlap (ACO) represents a treatable trait. ACO patients with eosinophilia are a potential group for therapy with biologicals.